William Bingham papers - Bingham, William, 1752-1804.
Primarily business correspondence of Bingham with Robert Morris and the firm of Willing & Morris, shipping merchants of Philadelphia, relating to Bingham's activities as Continental agent for the colonies in the West Indies (1776-1779) and to the commercial markets of both Europe and the United States during the Revolutionary period. Also includes a report to the Continental Congress (1799); a memorial to the frigate Confederacy (1780); a statement by Bingham on the U.S. financial system (1791); and miscellaneous undated documents. Correspondents include Benjamin Rush, James R. Reid, and Willing & Frances.
Trader, privateer owner, banker, and U.S. senator from Pennsylvania.
Collection material in English.
Keywords: Morris, Robert, -- 1734-1806 -- Correspondence; Reid, James R. -- Correspondence; Rush, Benjamin, -- 1746-1813 -- Correspondence; United States. -- Continental Congress; Confederacy (Frigate); Willing & Frances -- Correspondence; Willing & Morris (Philadelphia, Pa.) -- Correspondence; United States -- Commerce; United States -- Economic policy; United States -- History -- Revolution, 1775-1783.; West Indies -- Commerce; Bankers; Senators, U.S. Congress -- Pennsylvania; Shipowners; Traders